2015
DOI: 10.1371/journal.pntd.0004036
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo MRI Assessment of Hepatic and Splenic Disease in a Murine Model of Schistosmiasis

Abstract: BackgroundSchistosomiasis (or bilharzia), a major parasitic disease, affects more than 260 million people worldwide. In chronic cases of intestinal schistosomiasis caused by trematodes of the Schistosoma genus, hepatic fibrosis develops as a host immune response to the helminth eggs, followed by potentially lethal portal hypertension. In this study, we characterized hepatic and splenic features of a murine model of intestinal schistosomiasis using in vivo magnetic resonance imaging (MRI) and evaluated the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
(66 reference statements)
0
13
1
Order By: Relevance
“…The low contrast provided by unstained tissue is also a factor which precludes imaging of soft tissue in vivo at histological resolution. Magnetic resonance imaging (MRI), which is amenable to in vivo imaging, has been used to analyse parasite-induced pathology in whole animals (Voieta et al 2010 ; Masi et al 2015 ). However, MRI has a spatial resolution approaching 25–100 µ m in the most powerful magnetic fields (Shapiro et al 2004 ; de Kemp et al 2010 ), and no meaningful morphological information about tissue structure can be gathered below this threshold.…”
Section: What Parasitological Questions Could μ Ctmentioning
confidence: 99%
“…The low contrast provided by unstained tissue is also a factor which precludes imaging of soft tissue in vivo at histological resolution. Magnetic resonance imaging (MRI), which is amenable to in vivo imaging, has been used to analyse parasite-induced pathology in whole animals (Voieta et al 2010 ; Masi et al 2015 ). However, MRI has a spatial resolution approaching 25–100 µ m in the most powerful magnetic fields (Shapiro et al 2004 ; de Kemp et al 2010 ), and no meaningful morphological information about tissue structure can be gathered below this threshold.…”
Section: What Parasitological Questions Could μ Ctmentioning
confidence: 99%
“…The first MRI study of S. mansoni infected mice[94] used anatomical MRI and identified a patchy liver pattern assigned to fibrosis at histology. A longitudinal MRI study of this model[95] revealed anatomical signs of PH (liver, spleen and portal vein enlargement) and contrast-enhancement of fibrotic liver lesions. Furthermore, this study proposed that quantitative mapping of the transverse T 2 relaxation time constant could be used to noninvasively assess fibrosis[95].Concluding remarksAssessment of HSS morbidity and treatment monitoring would benefit from non-invasive imaging methods allowing reliable fibrosis staging and estimation of vascular dysfunction (see outstanding questions).…”
mentioning
confidence: 93%
“…A longitudinal MRI study of this model[95] revealed anatomical signs of PH (liver, spleen and portal vein enlargement) and contrast-enhancement of fibrotic liver lesions. Furthermore, this study proposed that quantitative mapping of the transverse T 2 relaxation time constant could be used to noninvasively assess fibrosis[95].Concluding remarksAssessment of HSS morbidity and treatment monitoring would benefit from non-invasive imaging methods allowing reliable fibrosis staging and estimation of vascular dysfunction (see outstanding questions). Quantitative methods, which have been successfully evaluated on human fibrotic and cirrhotic liver (USG elastography, MRE, 31 P-MRS, ASL, perfusion PET …) or in experimental schistosomiasis (T 2 mapping) have a potential for clinical/human schistosomiasis assessment provided the equipment is available.…”
mentioning
confidence: 93%
“…Moreover, the characterization of a mouse model of schistosomiasis using MRI demonstrated that this in vivo imaging technique is capable of monitoring liver damage during the course of the disease 26 . The pathological findings obtained in this MRT study were consistent with known characteristics of infected people, confirming the convenience of MRI imaging as an appropriate instrument to detect schistosomiasis and determine the efficacy of new developed therapies 26 . In light of these results, we assume that a combined use of PET/CT and MRI could be a beneficial technique for clinicians and researchers to visualize and characterize the worm load in infected individuals and to evaluate new treatments for schistosomiasis in vivo.…”
mentioning
confidence: 99%